Discordance between pediatric self‐report and parent proxy‐report symptom scores and creation of a dyad symptom screening tool (co‐SSPedi). (21st June 2020) - Tomlinson, Deborah; Plenert, Erin; Dadzie, Grace; Loves, Robyn; Cook, Sadie; Schechter, Tal; Furtado, Jennifer; Dupuis, L. Lee; Sung, Lillian
Abstract: Symptom Screening in Pediatrics Tool (SSPedi) (age 8‐18 years) and mini‐SSPedi (age 4‐7 years) can be used to self‐report and proxy‐report bothersome symptoms in pediatric patients receiving cancer treatments. There are limitations of sole child self‐report or proxy‐report. An approach in which children and parents complete symptom reports together may be useful. The aim of our study was to describe discordance between child self‐report and parent proxy‐report symptom scores, and to determine how these scores compare to an approach in which reporting is performed together (co‐SSPedi). Children and parents completed SSPedi or mini‐SSPedi separately. Discordant symptoms were shared with respondents and discussed. Next, the dyad completed co‐SSPedi together and were asked which approach they preferred. Discordance was evaluated for each symptom and was defined as a difference of at least 2 points on an ordinal scale ranging from 0 (not at all bothered) to 4 (extremely bothered). Of the 48 enrolled dyads (children, median age, 10.8 years; 54.2% male), 41 (85.4%) had discordance in at least one symptom. There was no clear pattern in discordance by age group. When a dyad approach was used, more co‐SSPedi scores agreed with the original child self‐report scores (59 dyads, 56.2%) compared to original parent proxy‐report scores (15 dyads, 14.3%) for discordant symptoms. Forty‐three (89.6%) dyads preferred to complete SSPedi together. Future work should evaluate the psychometric properties of co‐SSPedi. Abstract : Discordance is common between child self‐report and parent proxy‐report of symptom in children receiving cancer treatments, with no clear pattern in discordance by whether the symptom was subjective or objective, nor was there a clear pattern by age group. When a dyad approach was used, more scores agreed with the original child self‐report scores compared to original parent proxy‐report scores for discordant symptoms.